2020
DOI: 10.1101/2020.05.19.20101832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serologic responses to SARS-CoV-2 infection among hospital staff with mild disease in eastern France

Abstract: Background: The serologic response of individuals with mild forms of SARS-CoV-2 infection is poorly characterized. Methods: Hospital staff who had recovered from mild forms of PCR-confirmed SARS-CoV-2 infection were tested for anti-SARS-CoV-2 antibodies using two assays: a rapid immunodiagnostic test (99.4% specificity) and the S-Flow assay (~99% specificity).The neutralizing activity of the sera was tested with a pseudovirus-based assay. Results: Of 162 hospital staff who participated in the investigation, 16… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 20 publications
4
69
0
Order By: Relevance
“…In this study, we found that almost 10% of patients with mild COVID-19 did not develop detectable anti-SARS-CoV-2 IgG in serum as evaluated by assays used in clinical practice. Previous studies have similarly failed to detect IgG antibodies in patients with mild disease [24][25][26], but due to short follow-up (less than 25-50 days) no conclusions regarding the proportion of patients who do not seroconvert have been made in the belief that antibody levels become detectable later in time. We show that despite 90 days or more PSO, not all patients develop detectable levels of IgG in these assays.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we found that almost 10% of patients with mild COVID-19 did not develop detectable anti-SARS-CoV-2 IgG in serum as evaluated by assays used in clinical practice. Previous studies have similarly failed to detect IgG antibodies in patients with mild disease [24][25][26], but due to short follow-up (less than 25-50 days) no conclusions regarding the proportion of patients who do not seroconvert have been made in the belief that antibody levels become detectable later in time. We show that despite 90 days or more PSO, not all patients develop detectable levels of IgG in these assays.…”
Section: Discussionmentioning
confidence: 96%
“…Neutralising antibody responses correlated with disease severity in all studies in which this association was tested. 7,43,49,66,76,85,87,[96][97][98] Importantly, the few studies that investigated asymptomatic cases found those individuals were considerably less likely to develop detectable serum neutralising antibody responses than cases with symptoms. With regard to age and sex, evidence was mixed and a limitation across all papers was a lack of statistical adjustment for severity.…”
Section: Correlates Of Neutralising Antibody Productionmentioning
confidence: 99%
“…159 Antibody titre • Ten studies reported a higher titre of neutralising antibodies in more clinically severe cases. 7,43,49,66,85,87,[95][96][97][98]…”
Section: Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…3c), this finding is intriguing. Indeed, several public events resulted in large case clusters, the so-called superspreading events, that triggered epidemic bursts in France 33 , South Korea 34 or the U.S. 35 . A plausible explanation for not detecting the effectiveness of cancelling public events is that datadriven models, including ours, better capture the cumulative effect of more frequent events such as gatherings than the massive effect of much rarer events such as superspreading public events.…”
Section: Discussionmentioning
confidence: 99%